Contribuição ao estudo do comportamento da solubilidade dos ácidos bórico, benzóico e salicílico em misturas eletrolíticas - Pires, Ricardo Francisco (2011)
The Knowledge of the solubility of an electrolyte in a solvent or a mixture of solvents is extremely important for the chemical, pharmaceutical and food industry and also in the design of some industrial equipment. Moreover, this knowledge is important for modeling studies for the prediction of solubility data. In this work the solubility of benzoic, boric and salicylic acid in a pure solvent or a mixture of solvent + electrolyte (salt or vitamin) was determined experimentally. It was evaluated twenty-two systems, with no formation of two liquid phases. Measurements were performed in the temperature range from 293.0 to 313.0 K at atmospheric pressure constant. A direct method was employed to obtain the experimental data. The experimental equipment used consisted of Pyrex glass jacketed vessels connected in series, called cells, connected by a rubber hose and connected to a thermostatic bath. The samples were withdrawn only from the supernatant liquid mixture with a glass syringe and analyzed by gravimetry and spectrophotometry or titration. As results of this study, experimental solubility values of benzoic, boric and salicylic acid in electrolyte mixture were obtained at constant temperature and atmospheric pressure. In addition to experimental studies, it was possible to correlate the experimental data by estimating parameters of rational equations available in literature and conveniently modified to fit the data of this work. The adjusted results were compared with the data obtained experimentally for the acid solubilities. The results of pure solvent-soluble electrolyte showed good agreement with the literature results (maximum deviation of 11.5%). Original data for solubility were obtained in this work. Some solubility values in mixtures of acids were used to prepare electrolyte solutions tested in inhibition of orange s fungi growth. Most of cases, the tested acids showed satisfactory results in inhibiting the growth of the fungus and the benzoic acid presented the best results among the acids tested.